Optimalisasi Sanitasi Lingkungan di Pasar Mardika Kota Ambon - Mane, Sundari; Riry, Robert Berthy; Manakane, Susan Evelin (JENDELA PENGETAHUAN, 2026)
Market sanitation is a crucial aspect of public health and urban community welfare. The Mardika Market in Ambon City faces major challenges in hygiene management due to limited facilities, low hygienic awareness, and weak institutional coordination. This study aims to analyze the market’s sanitation conditions, identify inhibiting factors, and formulate optimization strategies based on community participation and local public policy. A qualitative descriptive approach was employed through observations, in-depth interviews, and documentation with traders, visitors, and market managers. Findings show that only 46% of sanitation facilities function properly, 62% of drainage systems are blocked, and only 36% of traders regularly maintain cleanliness. Community-based and institutional strengthening strategies were effective in improving sanitation management. Integrating Maluku’s socio-cultural values such as mutual cooperation becomes essential for building a sustainable sanitation system. This study enhances understanding of eco-social public policy.